Pembinaan dan Pengembangan UMKM dengan Teknik-Teknik Akuntansi Manajemen Pada UMKM Sus Tenun Lintau - Susriyati, Susriyati; Harma, Beni (LPPM Universitas Dharma Andalas, 2024)
Founding at the MSME Sus Tenun Lintau located in Jorong Seroja, Nagari Lubuak Jantan, Kecamatan Lintau Buo Utara, Kabupaten Tanah Datar. This UMKM was founded in 2022. This MSME produces based on orders because constrained in terms of capital and marketing, difficult to sell because this product is too expensive even though price of the raw materials is also expensive. Based on these obstacles, guidance with management accounting techniques is very important to increase the efficiency and productivity of these MSMEs, Cost of production (HPP) is the cost incurred to produce one unit of product. COGS can be calculated by considering raw material costs, weaving costs, administrative costs, and other costs related to production. By calculating COGS, MSMEs can find out the costs required to produce products, so they can make better decisions in setting selling prices and better optimize production and distribution processes to increase efficiency and profits.